Cardiovascular disease and male sexual dysfunction - Miner, Martin (Asian J Androl, 2015)
Erectile dysfunction (ED) is a form of sexual dysfunction that is estimated to affect > 30% of men between the ages of 40 and 70. As a result of an improved understanding about the pathophysiology of ED and improved treatment options, an increasing number of men are presenting for evaluation than several decades ago. In fact, many of these men are visiting their health care professional for the first time with ED as their primary complaint. Most of these men are unaware of the link between ED and cardiovascular disease (CVD).